CERN decelerating RFQ for antiprotons - Bylinsky, Yu.; Lombardi, A.M.; Pirkl, W. (Вопросы атомной науки и техники, 2001)
A new decelerating radio frequency quadrupole (RFQD) has been put in operation at CERN. It decelerates either protons or antiprotons from a momentum of 100 MeV/c (kinetic energy 5.33 MeV) down to a kinetic energy variable between ~10 keV and 120 keV. A novel feature is the implementation of a floating internal RF structure, mounted on HV insulators. It allows continuous post-deceleration or acceleration from the nominal energy of 63 keV by a high tension DC bias applied to accelerating electrodes. A description of the system is given, followed by reports on the first operating experience with the ASACUSA experiment, dedicated performance measurements and consolidation progress.